Estudo da cristalização de parafinas em sistemas solventes/tensoativos/água - Gomes, Erika Adriana de Santana (2009)
The WAT is the temperature at the beginning of the appearance of wax crystals. At this temperature the first wax crystals are formed by the cooling systems paraffin / solvents. Paraffins are composed of a mixture of saturated hydrocarbons of high molecular weight. The removal of petroleum from wells and the production lines means a surcharge on produced oil, thus solubilize these deposits formed due to modifications of thermodynamics has been a constant challenge for companies of oil exploration. This study combines the paraffin solubilization by microemulsion systems, the determination of WAT systems paraffin / solvent and performance of surfactant in reducing the crystallization. We used the methods: rheological and the photoelectric signal, validating the latter which was developed to optimize the data obtained due to sensitivity of the equipment used. Methods developed for description of wax precipitation are often in poor agreement with the experimental data, they tend to underestimate the amount of wax at temperatures below the turbidity point. The Won method and the Ideal solution method were applied to the WAT data obtained in solvent systems, best represented by the second interaction of Won method using the solvents naphtha, hexane and LCO. It was observed that the results obtained by WAT photoelectric signal when compared with the viscosity occur in advance, demonstrating the greatest sensitivity of the method developed. The ionic surfactant reduced the viscosity of the solvent systems as it acted modifying the crystalline structure and, consequently, the pour point. The curves show that the WAT experimental data is, in general, closer to the modeling performed by the method of Won than to the one performed by the ideal solution method, because this method underestimates the curve predicting the onset of paraffin hydrocarbons crystallization temperature. This occurs because the actual temperature measured was the crystallization temperature and the method proposes the fusion temperature measurement.